Morphological characteristics and correlation of chronic hematogenous osteomyelitis with latent clinical course (Garre type) - Hryhorovskyi, Valeriy; Hrytsai, Mykola; Hordii, Andrew; Lyutko, Olga; Hryhorovska, Anastasiya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
One of the clinico-morphological variants of osteomyelitis with latent course is sclerosing hematogenous osteomyelitis of the Garre type. Objective: on the basis of pathomorphological and gradation-morphometric studies of bone lesion, establish statistical differences between individual forms and correlation links between the morphological indices of lesions of the bone of patients with sclerosing hematogenous osteomyelitis. Methods: fragments of affected bones of 25 patients with clinically established sclerosing hematogenous osteomyelitis were studied. On the basis of pathohistological study, morphological indices were identified, with the use of which gradation-frequency and correlation analysis of nonparametric data was carried out with the calculation of the association coefficient. Results: despite the general similarity of morphological manifestations, differences in the forms of sclerosing hematogenous osteomyelitis were established: about ⅔ of all cases corresponded to the fibrosing form of the focus without the presence of exudative inflammation. In the remaining cases, in addition to fibrosis and osteosclerosis, the foci of osteomyelitis contained microabscesses, within which small sequestrations were found. Forms of foci of sclerosing hematogenous osteomyelitis can eventually move from one to another. Between the fibrotic with micro-abscess formation of sclerosing hematogenous osteomyelitis and the presence of microsequesters in the microabscesses, a reliable positive correlation was found between the mean force (ra= +0.620). Sequesters in tissues were not observed in the foci of fibrosis. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> sclerosing hematogenous osteomyelitis is a clinical variant with a latent course mainly in adolescent patients, in which there is no macrodefective damage to the bone marrow and bone tissue by an infectious inflammatory process, namely: large abscesses, significant sequestration, parasseous abscesses and fistulas.